Development of tax monitoring in the Russian Federation: trends, issues, and prospects - Koroleva, Lyudmila Pavlovna (Теоретическая и прикладная экономика, 2025)
The article investigates the applied aspects of the implementation and development of tax monitoring in the Russian Federation. The research objective is to identify trends, problems, and development prospects of tax monitoring in the Russian Federation based on a comprehensive analysis of institutional transformations and existing statistical data. Special attention is given to assessing its demand among the largest taxpayers based on the dynamics of the number and structure of monitoring participants by industry, the methods of information interaction used, taking into account the organizational features of activities and ownership structure, as well as the number of motivated opinions and the amount of taxes and fees settled by them. The potential impact of the digital transformation of tax monitoring on the state of internal control systems and risk management in organizations, as well as best practices for organizing information interaction and using modern technologies, has been examined. The research was conducted using general scientific methods, economic analysis methods (vertical and horizontal), and statistics (averages, specific indicators). The informational basis of the research consisted of the Tax Code of the Russian Federation and other regulatory acts, reports from the Federal Tax Service of Russia, large companies participating in tax monitoring, and the results of studies on the maturity of internal control and risk management systems conducted by consulting companies. Conclusions were drawn regarding the low proportion of the largest taxpayers who have transitioned to monitoring, as well as its low demand from large private businesses without government involvement. Trends in the development of tax monitoring for 2015–2025 are substantiated: increasing its accessibility; developing a risk-oriented approach by enhancing both the advantages for conscientious taxpayers and the monitoring control functions; and the digitalization of tax monitoring activities for both tax authorities and taxpayers. Problems reducing the demand for monitoring among taxpayers include high complexity and cost of entry; retention of limited effectiveness of motivated opinions; and limited effectiveness of the risk-oriented approach. As a result of studying the projects of tax authorities, prospects for its development have been identified. Elements of scientific novelty include the justified trends and prospects for the development of tax monitoring proposed by the author, as well as suggestions for addressing identified problems. Insufficient attention is paid to the development of joint compliance tools, which is a promising area for research.